Michaił Katkow — u początków myśli politycznej apologety rosyjskiego samodzierżawia - Szpoper, Dariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Mikhail Katkov (1818–1887), a leading Russian political journalist, began his career as a liberal fascinated by German philosophy, especially the views of Friedrich Wilhelm Joseph von Schelling. At that time, he represented a moderate pro-Polish attitude. After the outbreak of the January Uprising in 1863, on the pages of Moskowskije Wiedomosti, which he edited, he promoted the Russian state’s viewpoint in favour of the monarchy and full dimension of the Russian Empire’s state integrity, which led to his conservative position.
Keywords: Imperium Rosyjskie; Katkow, Michaił; liberalizm; konserwatyzm; powstanie styczniowe z 1863 roku; „Moskowskije Wiedomosti”; Schelling, Friedrich Wilhelm Joseph von; samodzierżawie